Contrasting Mechanisms of Interferon‐α Inhibition by Intravenous Immunoglobulin After Induction by Immune Complexes Versus Toll‐like Receptor Agonists. Issue 10 (24th September 2013) - Wiedeman, Alice E.; Santer, Deanna M.; Yan, Wei; Miescher, Sylvia; Käsermann, Fabian; Elkon, Keith B.
<x xml:space="preserve">Abstract</x> Objective Plasmacytoid dendritic cells (PDCs) produce high concentrations of interferon‐α (IFNα) following exposure to immune complexes containing nucleic acids. We previously reported that serum from healthy donors inhibits IFNα production by PDCs in response to systemic lupus erythematosus (SLE) immune complexes, and that inhibition is mediated, in part, by IgG. IgG is the major component of intravenous immunoglobulin and is well known to exert antiinflammatory properties. Although suppression of inflammation by the sialylated subfraction of IgG has been implicated in some models, the mechanism of IFNα inhibition by IgG and the importance of sialylation have not been studied. Methods SLE immune complexes or synthetic Toll‐like receptor (TLR) agonists were used to stimulate total or individual cell–depleted human mononuclear cell cultures in the presence or absence of IgG, Fc fragments, F(ab′)2 fragments, and their sialylated or unsialylated subfractions. Cytokines were quantified by enzyme‐linked immunosorbent assay. Results We identified 2 distinct mechanisms by which IgG inhibits IFNα production. First, IgG Fc fragments inhibited SLE immune complex–stimulated IFNα production via a sialic acid–independent mechanism, by inhibiting immune complex binding to Fcγ receptor IIa on PDCs. In contrast, the F(ab′)2 fragment of the sialylation‐enriched fraction of IgG inhibited TLR‐7 or TLR‐9 agonist–induced IFNα production but did not require the sialic acid residue itself. The inhibitory activity of IgG on TLR agonist–induced IFNα required monocyte production of prostaglandin E2, a potent suppressor of IFNα production by PDCs. Conclusion IgG attenuates IFNα production by PDCs by both cell surface receptor and intracellular pathways, depending on the nature of the inducing stimulus.